2012
DOI: 10.1002/psc.2403
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic peptides derived from an N‐terminal domain of the E2 protein of GB virus C in the study of GBV‐C/HIV‐1 co‐infection

Abstract: Synthetic peptides derived from GB virus C (GBV-C) have previously been studied in our group for the development of new systems capable of diagnosing diseases caused by this humanotropic virus. We also recently described specific peptide domains of the E2 envelop protein of GBV-C that have the capacity to interfere with the HIV-1 fusion peptide, produce a notable decrease in cellular membrane fusion, and perturb HIV-1 infectivity in a dose-dependent manner. The present work discloses the design and synthesis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…in the field of GB virus C, Herpes simplex, and human coronaviruses. They concluded that antigenic peptides could be considered useful tools for designing new diagnostic systems with often sensitivities in the range of low- picomolar concentrations of mAbs and with a high specificity [38,39]. However, while evaluating our results, we were absolutely aware of the shortcomings of the initial experiments.…”
Section: Discussionmentioning
confidence: 97%
“…in the field of GB virus C, Herpes simplex, and human coronaviruses. They concluded that antigenic peptides could be considered useful tools for designing new diagnostic systems with often sensitivities in the range of low- picomolar concentrations of mAbs and with a high specificity [38,39]. However, while evaluating our results, we were absolutely aware of the shortcomings of the initial experiments.…”
Section: Discussionmentioning
confidence: 97%
“…Dendrimers are well-de ned (monodisperse) synthetic globular polymers with a range of interesting chemical and biological properties [224,[240][241][242]. Chemical properties include the presence of multiple accessible surface functional groups that can be used for coupling biologically relevant molecules and methods allowing precise heterofunctionalization of surface groups.…”
Section: Dendrimers For Vaccine and Immunostimulatorymentioning
confidence: 99%
“…The E2 envelope glycoprotein appears to inhibit the earlier steps of HIV infection, due to an internal fusion peptide that inhibits gp41 fusion to the cell targets [5]. The use of small peptides derived from GBV-C envelope proteins has thus been suggested as a strategy to inhibit HIV-infection [6][7][8].…”
Section: Introductionmentioning
confidence: 99%